FOOD SECURITY IN A REGIONAL PERSPECTIVE A View from 'Food Deficit' Kerala - K.P. Kannan (Centre for Development Studies, 2000)
The paper examines the question of food security viz-a-viz food availability and self sufficiency in production. Given the cropping pattern in Kerala it is unrealistic to expect food self-sufficiency. However, through a pro-poor public policy regime, Kerala has been able to enhance food security considerably. This situation is currently being challenged as a result of a shift in policy of the Central Government with regard to the Public Distribution System in the country. This could lead Kerala to accelerating its fiscal crisis should it decide to continue with the current system of food security.